Palladium-Catalyzed Phosphine-Free Direct C–H Arylation of Benzothiophenes and Benzofurans Involving MIDA Boronates - Wang, Zhiwei; Li, Yabo; Yan, Beiqi; Huang, Mengmeng; Wu, Yangjie (Synlett, 2015)
With high regioselectivity, a series of benzoheterocyclic compounds were synthesized via palladiium-catalyzed phosphine-free C–H arylation of benzothiophenes/benzofurans with aryl MIDA boronates at 30–50 °C in moderate to excellent yields. MIDA boronates were used in C–H arylation of heterocycles for the first time. Under the optimal conditions, the benzothiophenes could be transformed into the β-arylbenzothiophenes, and the benzofurans gave only α-aryl-substituted products.
Keywords: C–H arylation; benzothiophene; benzofuran; MIDA boronate; bis(alkoxo)palladium(II) complex